Geneza oraz główne kierunki działalności zakładu ubezpieczeń wzajemnych w Poznaniu - Krotoska, Maria (Wydział Prawa i Administracji UAM, 1973)
The Mutual Insurance Company, founded in Poznań in 1932, had to overcome a lot of difficulties in its activity in the territories of the then Pomorze and Poznań province, and that was caused by economic conditions, among others by strong competition of foreign insurance companies. All the same the Mutual Insurance Company in Poznań tried to extend the range of its activity and to strengthen its financial basis. During the first two years of its activity the Company effected only fire and hail insurance, after that period it extended the range of its activity by undertaking insurance against theft and liability insurance. In the Pomorze and Poznań province there was strong social demand for insurance protection of the middle-sized and small farms which represented risks bearing little profit and therefore were unattractive for an insurance office. In agriculture insurance protection was far from full and general and The Mutual Insurance Company in Poznań tried to make up the deficiency.
The Mutual Insurance Company in Poznań. Its Origin and Range of Activity